Förster resonance energy transfer imaging in vivo with approximated radiative transfer equation - Soloviev,VY; McGinty,J; Stuckey,DW; Laine,R; Wylezinska-Arridge,M; Wells,DJ; Sardini,A; Hajnal,JV; French,PMW; Arridge,SR (Applied Optics, 2011)
We describe a new light transport model, which was applied to three-dimensional lifetime imaging of Förster resonance energy transfer in mice in vivo. The model is an approximation to the radiative transfer equation and combines light diffusion and ray optics. This approximation is well adopted to wide-field time-gated intensity-based data acquisition. Reconstructed image data are presented and compared with results obtained by using the telegraph equation approximation. The new approach provides improved recovery of absorption and scattering parameters while returning similar values for the fluorescence parameters.